Игра с нормой в интернет-мемах - Wilk, Gabriela (Studia Rossica Posnaniensia, 2024)
There is no doubt that internet communication is characterized by language democratization, which is particularly evident in the case of a genre such as internet memes. In the process of meme creation, the norms are quite often exceeded. Particularly noticeable are deviations from the orthographic, punctuation, grammatical, or stylistic norms (a large number of swear words). A significant part of these deviations is intentional, as they testify to the linguistic creativity of the meme authors who aim to achieve a humorous effect. The purpose of this article is to present how deviations from the norms are used in Russian internet memes. It is also pointed out that memes addressing the problem of linguistic correctness humorously can be found on the internet. The analysis showed that they could be a specific form of fighting against violations of the linguistic norms in online communication. By ridiculing typical mistakes in the contemporary Russian language, they popularize normative forms.